Preparation for teaching. A manual with exercises in curriculum development - Mattson, H. A. (Information Collection and Exchange Division, Peace Corps, 1985)
The purpose of this manual is to provide a technique to help teachers better prepare for a teaching career in industrial education. Specifically, this manual, including the exercises, was developed to be used in weekly seminars for students enrolled in the St. Vincent Teachers' College. It may also be used for staff development on an individual basis and serve as a pilot programme for those preparing to teach in multi-vocational centres in St. Vincent. The manual provides a process through which the teacher can prepare for a teaching career by focusing on curriculum development in the area of industrial education. Along with basic information, a series of exercises are presented that involve contact with representatives of local business and industry and teacher trainers, as well as the study of journals and reference materials that may be available. Sections include an overview of curriculum development, an outline of the course of study, development of lesson plans, project selection in industrial arts, and a checklist for programme improvement
Keywords: Teacher education